Key Factors Affecting Reproductive Success of Thoroughbred Mares and Stallions on a Commercial Stud Farm. Issue 2 (27th January 2016) - Lane, EA; Bijnen, MLJ; Osborne, M; More, SJ; Henderson, ISF; Duffy, P; Crowe, MA
Contents: To evaluate factors contributing to fertility of thoroughbred mares, data from 3743 oestrous periods of 2385 mares were collected on a large thoroughbred farm in Ireland. Fourteen stallions (mean age 8.3 years; range 4–15 years) had bred 2385 mares (mean age 9.4 years; range 3–24 years). Maiden mares accounted for 12%, mares with a foal at foot for 64%, and barren, slipped or rested mares for 24% of the total. The mean pregnancy rate per cycle was 67.8% (68.6% in year 1 and 66.9% in year 2). Backward stepwise multivariable logistic regression analysis was utilized to develop two models to evaluate mare factors, including mare age, reproductive status, month of foaling, dystocia, month of cover, foal heat, cycle number, treatments, walk‐in status and stallion factors including stallion identity, stallion age, shuttle status, time elapsed between covers and high stallion usage on the per cycle pregnancy rate and pregnancy loss. Old age (p < 0.001) and cover within 20 days post‐partum (p < 0.003) were associated with lowered pregnancy rates. High mare age (p < 0.05) and barren, slipped or rested reproductive status (p = 0.05) increased the likelihood of pregnancy loss. Uterine inflammation or infection, if appropriately treated, did not affect fertility. Only high usage of stallions (used more than 21 times in previous week) was associated with lowered (p = 0.009) pregnancy rates. However, shuttle stallions were more likely to have increased (p = 0.035) pregnancy survival, perhaps reflecting a bias in stallion selection. In conclusion, mare age exerted the greatest influence on fertility; nonetheless, thoroughbreds can be effectively managed to achieve high reproductive performance in a commercial setting.